أثر المؤشرات العالمية في اتخاذ قرار الاستثمار الأجنبي المباشر: دراسة مقارنة - شهاب، سعد عجيل; متري، علاء صابر حليم (جامعة أسيوط - كلية التجارة, 2015)
There is no doubt that foreign direct investment is of great importance because it is one of the most prominent foreign channels to finance economic activities and projects, it plays a significant and important role in increasing the flow of foreign capital, in addition to creating new jobs, as well as improving the balance of payments by increasing export opportunities and the reduction of import, in addition to being an important tool for the transfer of advanced technology and training of local personnel on the use of advanced production and thus contribute to the acceleration of economic development very quickly. Due to the growing importance of foreign direct investment in the world, it states keen in general and developing, in particular, to attract this kind of investment, and through appropriate him to the climate, but the reality is that there is a disparity in the volume of foreign direct investment between both countries developed and developing countries, the developed states despite the lack of need for foreign investment as much need of developing countries have, but with the largest share of these investments, and this is due to the availability of appropriate investment climate in these countries is the opposite of developing countries. Hence, our study begins to try to find a way to help developing countries in the appropriate environment for foreign direct investment saving, have been addressed to the international indicators, which are of great importance in the field of the appropriate environment for investors, especially foreign availability so the international indicators such as the International Competitiveness Index and globalization and the Human Development Index and other indicators serve as a great extent in measuring the appropriate climate for foreign direct investment in the countries covered by the indicators provide. The study came out of the conclusions of the task of them, that there is a direct correlation between the international indicators and inflows of foreign direct investment, and Competitiveness Index fit to be an accurate measure of the extent of the right climate for foreign direct investment offers. In light of the findings, the researchers made several proposals, including, to the local and foreign investors guided by the Global Competitiveness Index published annually in the process of assessing the suitability of the investment climate to attract foreign direct investment, and the governments of developing countries, including Iraq and elsewhere, giving the Global Competitiveness Index More attention.
مما لا شك فيه أن الاستثمار الأجنبي المباشر يحظى بأهمية كبيرة لكونه أحد أهم وأبرز القنوات الخارجية لتمويل النشاطات والمشاريع الاقتصادية فهو يؤدي دورا كبيرا ومهما في زيادة تدفق رؤوس الأموال الأجنبية بالإضافة إلى خلق فرص عمل جديدة، وكذلك تحسين ميزان المدفوعات عن طريق زيادة فرص التصدير والحد من الاستيراد هذا بالإضافة إلي كونه أداة مهمة لنقل التكنولوجيا المتطورة وتدريب العامليين المحليين على استخدام وسائل الإنتاج المتقدمة وبالتالي فإنه يسهم في دفع عجلة التنمية الاقتصادية بسرعة كبيرة. ونظرا لتزايد أهمية الاستثمار الأجنبي المباشر على مستوي العالم، فقد حرصت الدول بصورة عامة والنامية بصورة خاصة على جذب هذا النوع من الاستثمار وذلك عن طريق تهيئة المناخ الملائم له، إلا أن الواقع يشير إلي أن هناك تباينا في حجم الاستثمارات الأجنبية المباشرة بين كل من الدول المتقدمة والنامية فالدول المتقدمة علي الرغم من عدم حاجتها للاستثمارات الأجنبية بقدر حاجة الدول النامية لها، إلا أنها صاحبة النصيب الأكبر من هذه الاستثمارات وهذا عائد إلي توفر المناخ الاستثماري الملائم في هذه الدول وهو عكس الدول النامية. ومن هنا تنطلق دراستنا لمحاولة إيجاد وسيلة تساعد الدول النامية في توفير المناخ الملائم للاستثمار الأجنبي المباشر وقد تم التطرق إلي المؤشرات الدولية والتي لها أهمية كبيرة في مجال توفر المناخ الملائم للمستثمرين وخاصة الأجانب، لذا فإن المؤشرات الدولية ومنها مؤشر التنافسية الدولية ومؤشر العولمة ومؤشر التنمية البشرية وغيرها من المؤشرات تصلح إلي حد كبير في قياس مدي توفر المناخ الملائم للاستثمار الأجنبي المباشر في الدول التي تشملها المؤشرات. وقد خرجت الدراسة باستنتاجات مهمة منها أن هناك علاقة طردية بين المؤشرات الدولية وتدفقات الاستثمارات الأجنبية المباشرة وأن مؤشر التنافسية يصلح أن يكون مقياسا دقيقا لمدي توفر المناخ الملائم للاستثمار الأجنبي المباشر. وفي ضوء النتائج خرج الباحثان بعدة مقترحات من بينها أن على المستثمرين المحليين والأجانب الاسترشاد بمؤشر التنافسية العالمية الذي ينشر سنويا في عملية تقييم مدي ملاءمة مناخ الاستثمار في جذب الاستثمارات الأجنبية المباشرة، وعلي حكومات البلدان النامية ومنها العراق وغيرها، إعطاء مؤشر التنافسية العالمية المزيد من الاهتمام.
Keywords: الاستثمار الأجنبي المباشر -- الدول النامية